DEGRADATION OF AQUEOUS RHODAMINE B BY CATALYSIS ZONE EXTENSION OF MODIFIED DYES SENSITIZED SOLAR CELL. - Sarwana, Wirya (Jurnal TAMBORA, 2017)
A modified dyes sensitized solar cell (DSSC) having catalysis zone have been successfully developed. The modified DSSC comprise of DSSC zone, employing a rhodamine B as the sensitizer, and catalysis zone, a simple an extension of the TiO2 nanotube film support which was not covered by dyes. The TiO2 nanotube was prepared by rapid breakdown anodization (RBA) method followed by heating treatment of obtained amorphous TiO2 nanotube, and charactetization by UV-Vis DRS, XRD, and SEM. Briefly, the obtained TiO2 has a bundling nanotube morphology, crystalline phase and typical band gap of anatase and rutile mixture (depend on heating temperature). The catalysis zone was tested to treat a water sample containing organic chemical (rhodamine B), as a pollutant model. Test results indicated that the catalysis zone enable to eliminate of rhodamine in the treated water, due to subsequent process starting by generation of super oxide (.O2-) in adjacent TiO2 surface, leading to hydroxyl radical which in turn degrade the rhodamine B. This result indicate that the injected electron from dyes, upon visible light absorption, to conduction band of TiO2 in DSSC zone was successfully migrated to TiO2 surface in catalysis zone.